Targeting Oxidative Stress Reduction and Inhibition of HDAC1, MECP2, and NF-kB Pathways in Rats With Experimentally Induced Hyperglycemia by Administration of Thymus marshallianus Willd. Extracts - Sevastre-Berghian, Alexandra C.; Ielciu, Irina; Mitre, Andrei Otto; Filip, Gabriela A.; Oniga, Ilioara; Vlase, Laurian; Benedec, Daniela; Gheldiu, Ana-Maria; Toma, Vlad A.; Mihart, Bianca; Mihuţ, Andra; Bâldea, Ioana; et al. (Frontiers in Pharmacology, 2020)
Effects of two lyophilized extracts obtained from the aerial parts of Thymus marschallianus harvested from wild flora (TMW) and from culture (TMC) on experimental-induced hyperglycemia by streptozotocin (STZ) administration in Wistar rats were evaluated. Polyphenolic composition of extracts was evaluated by spectrophotometrical and LC-MS methods. In vitro antioxidant capacity assays (DPPH, FRAP, EPR) were performed in order to preliminary establish the ability of tested samples to protect against free radical induced damage. Afterwards, the effects of these extracts were assessed in vivo on rats with experimental-induced hyperglycemia. Oxidative stress biomarkers, phosphorylated transcription factor subunit of nuclear kappaB (NF-kB) p65, methyl CpG binding protein (MECP) 2 and histone deacetylase 1 (HDAC1) expressions in hippocampus and frontal lobe were assessed. Open Field Test (OFT) and Elevated Plus Maze (EPM) were conducted on tested animals. Malondialdehyde (MDA) levels and HDAC1and MeCP2 expressions increased significantly in hippocampus (p<0.05) and frontal lobe (p<0.001) of diabetes group compared to the control group in parallel with decreasing of GSH/GSSG ratio. TMW and TMC administration reduced blood glucose levels and diminished lipid peroxidation, HDAC1 expression and enhanced antioxidant capacity in frontal lobe. TMW improved central locomotion of rats, increased phospho-NFkB p65 and diminished MECP2 expressions in hippocampus. Both tested samples exerted beneficial effect by increasing the antioxidant defense. Our findings indicate that administration of these extracts might represent a good option in the treatment of diabetes and its complications.